2020
DOI: 10.1177/1945892420920479
|View full text |Cite
|
Sign up to set email alerts
|

Medical Liability in Sinus Surgery: A Westlaw Database Analysis From 2000 to 2017

Abstract: Background Medical malpractice occurs when a hospital or health-care provider through negligent act or omission results in an injury to a patient. More than 50% of otolaryngologists have faced at least 1 claim, with rhinology being the most litigated subspecialty. This study aims to analyze medical litigation trends in Rhinology from 2000 to 2017 in the United States. Methods The Westlaw database was reviewed from 2000 to 2017. Data were compiled on the demographics of the plaintiffs, procedures, nature of dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…For comparison, endoscopic sinus surgery has relatively similar complication rates and case volumes in the United States but is litigated much more frequently. 17 However, of the Westlaw database cases that went to trial, a relatively high percentage of cases were ruled in favor of the plaintiff (4 orbital decompression cases or 57% and 2 DCR cases or 40%), with an average of $364 509 awarded in each case.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, endoscopic sinus surgery has relatively similar complication rates and case volumes in the United States but is litigated much more frequently. 17 However, of the Westlaw database cases that went to trial, a relatively high percentage of cases were ruled in favor of the plaintiff (4 orbital decompression cases or 57% and 2 DCR cases or 40%), with an average of $364 509 awarded in each case.…”
Section: Discussionmentioning
confidence: 99%
“…As the use of this tool has become more widely adopted, adverse events have increased to 19.5 events per year from the 12.6 annual average that was previously reported by Prince et al 11 Of the procedures performed, frontal sinus dilation was found to be most susceptible to adverse events, including CSF leak and device retention. In a related study that looks at medical litigation in the field of rhinology over the last 2 decades, Shah et al 12 demonstrates a geographic trend toward higher rates of malpractice claims in states in which tort reform has not taken place. The majority of allegations included failure to follow the standard of care and improper performance, whereas the largest payouts included eye injuries and intracranial complications.…”
mentioning
confidence: 99%